A comparison of the prevalence and risk factors of suicidal ideation and suicide attempts in two American Indian population samples and in a general population sample. (February 2014) - Bolton, Shay-Lee; Elias, Brenda; Enns, Murray W.; Sareen, Jitender; Beals, Janette; Novins, Douglas K.
The current study aimed to examine whether the prevalence and risk factors for suicidal ideation and attempts differ when comparing two American Indian reservation samples to the U.S. general population. Data were from the baseline nationally representative National Comorbidity Survey ( N  = 5, 877) and the representative American Indian Service Utilization, Psychiatric Epidemiology, Risk and Protective Factors Project (AI-SUPERPFP; N  = 3, 084). Face-to-face interviews were conducted using the fully structured World Health Organization Composite International Diagnostic Interview. American Indians from these Northern Plains and Southwest tribes appeared significantly less likely to have suicidal thoughts in their lifetime when compared with the general population, odds ratio (OR) of 0.49 (99% CI [0.36, 0.66]) and 0.36 (99% CI [0.25, 0.51]), respectively. However, members of the Northern Plains tribe were more likely to have attempted suicide in their lifetime compared with the general population (OR = 1.96, 99% CI [1.45, 2.65]). Suicide attempts without suicidal ideation were more common in the two American Indian samples than in the general population. In contrast, correlates of suicidal behavior appear quite similar when comparing the groups. Increased attention is needed to determine why rates of ideation and attempts may differ in American Indians when compared with the general population.